Analisis Kelayakan Coffee Sudut Temu di Kota Lhokseumawe Dengan Tools Payback Period, Net Present Value dan Internal Rate of Return - Misniah, Misniah Misniah; Nurlela, Nurlela Nurlela; Syamni, Ghazali .; Wahyuddin, Wahyuddin Wahyuddin (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This research aims to analyze the feasibility of meeting corner coffee in the city of Lhokseumawe using the tools' Payback period, Net Present Value (NPV), Internal Rate of Return (IRR) and Break Even Point (BEP). The research results show that based on financial analysis using the Payback Period (PP) method, the calculation results are 6 years and 4 months, where the return on investment is longer than the economic life of the business, namely 5 years. Based on financial analysis using the Net Present Value (NPV) method, the calculation results show that the corner coffee shop business is positive and feasible to develop with a discount factor (DF) level of 7%. Based on financial analysis using the Internal Rate of Return (IRR) method, the calculation result was 8.2%, so this business is feasible to develop because the IRR value is greater than the discount factor (DF) level of 7%. Based on a sensitivity analysis using an indicator of a 3-5% increase in variable costs, the results obtained are that the coffee shop business at the corner of Temu is still feasible to run up to a 5% increase. Keywords: PP, NPV, IRR and BEP